Combined pulmonary fibrosis and emphysema: a narrative review - Zeng, Wenjing; Liang, Binmiao; Ou, Xuemei (Frontiers in Medicine, 2025)
Combined pulmonary fibrosis and emphysema (CPFE) is defined as a clinical-radiological-physiological syndrome characterized by upper-lobe emphysema and fibrosis predominantly in the lower lobes. The diagnosis of CPFE remains challenging due to the opposing pathophysiological effects of emphysema and fibrosis, which can mask their characteristic clinical and imaging features. Although an international committee proposed standardized terminology for CPFE in 2022, uniform diagnostic criteria and optimal management strategies have not yet been established. Patients with CPFE exhibit reduced overall survival and higher mortality compared to those with chronic obstructive pulmonary disease (COPD) or idiopathic pulmonary fibrosis (IPF). This may be due to increased disease severity, as assessed by CT findings (the extent of fibrosis and emphysema), advanced age, and associated complications such as lung cancer, acute exacerbations, and pulmonary arterial hypertension. This narrative review synthesizes the literature on CPFE from 1990 to 2024, covering its historical background, epidemiology, pathogenesis, clinical presentation, diagnostic features (imaging and pulmonary function), disease course (diagnosis, prognosis, complications), and management.